2005
DOI: 10.1080/0305569042000310976
|View full text |Cite
|
Sign up to set email alerts
|

Student views concerning evidence and the expert in reasoning a socio‐scientific issue and personal epistemology

Abstract: This study investigated their views concerning evidence and expert opinion of 10th-grade students, accessed by an open-ended questionnaire in the context of a socio-scientific issue: the cause of flood disasters, and personal epistemology identified by the Learning Environment Preference Questionnaire (LEP). Students' responses to the open-ended questions showed that when thinking about the flood issue, most students rely heavily on direct and numerical data to draw their conclusions, while experts represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
(40 reference statements)
4
31
1
Order By: Relevance
“…The analysis of responses level zero of argumentation revealed that preservice teachers often had difficulty in providing adequate scientific evidence to support their claims; rather, they relied on personal experiences in their explanations. Preservice teachers' use of their personal opinions to address socioscientific issues rather than scientific data is also reported in past research (Albe, 2008;Hogan and Maglienti, 2001;Yang, 2005). For instance, Yang (2005) reported that students' reasoning modes are more driven by their personal epistemological perspective in environmental decision-making.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The analysis of responses level zero of argumentation revealed that preservice teachers often had difficulty in providing adequate scientific evidence to support their claims; rather, they relied on personal experiences in their explanations. Preservice teachers' use of their personal opinions to address socioscientific issues rather than scientific data is also reported in past research (Albe, 2008;Hogan and Maglienti, 2001;Yang, 2005). For instance, Yang (2005) reported that students' reasoning modes are more driven by their personal epistemological perspective in environmental decision-making.…”
Section: Discussionmentioning
confidence: 78%
“…Preservice teachers' use of their personal opinions to address socioscientific issues rather than scientific data is also reported in past research (Albe, 2008;Hogan and Maglienti, 2001;Yang, 2005). For instance, Yang (2005) reported that students' reasoning modes are more driven by their personal epistemological perspective in environmental decision-making. While relying on personal opinions may be desirable to initially reveal how students conceptual a given issue, the integration of appropriate content and disciplined arguments is the aim of the pedagogical end game.…”
Section: Discussionmentioning
confidence: 78%
“…From a traditional perspective scientific knowledge is believed to be objective, empirical, based on control of nature, universal, value-free and replicable. The post-positivist arguments related to nature of scientific knowledge question the absolute objectivity, universality and value-free assumptions and focus on the constructivist and contextual aspects of scientific knowledge (Pomeroy, 1993;Tsai, 2000;Yang, 2005).…”
Section: Epistemological Beliefsmentioning
confidence: 99%
“…In science education the notion of 'socio-scientific issues' has been introduced as a way of describing social dilemmas impinging on scientific fields (Gayford, 2002;Kolstoe, 2001;Sadler et al, 2004;Zeidler et al 2002, Yang, 2005. These are issues on which people have different opinions and which have implications in one or more of the following fields: biology, sociology, ethics, politics, economics and/or the environment.…”
Section: Socio-scientific Issuesmentioning
confidence: 99%